2010
DOI: 10.1093/cvr/cvq210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of competitive flow on wall shear stress in coronary surgery: computational fluid dynamics of a LIMA–LAD model

Abstract: Graft flow is highly dependent on the degree of competitive flow. High competitive flow was found to produce unfavourable WSS consistent with endothelial dysfunction and subsequent graft narrowing and failure. Partial competitive flow, however, may be better tolerated as it was found to be similar to the ideal condition of no competitive flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 31 publications
(30 reference statements)
1
69
0
5
Order By: Relevance
“…Later reports further confirmed these early observations (Katritsis et al, 2007;Nordgaard et al, 2010). Katritsis et al (2007) investigated the WSS oscillations based on the simulated artery bifurcation model comprising a straight tube, and their results showed that low wall shear stress occurred in the bifurcation locations.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Later reports further confirmed these early observations (Katritsis et al, 2007;Nordgaard et al, 2010). Katritsis et al (2007) investigated the WSS oscillations based on the simulated artery bifurcation model comprising a straight tube, and their results showed that low wall shear stress occurred in the bifurcation locations.…”
Section: Discussionmentioning
confidence: 66%
“…Katritsis et al (2007) investigated the WSS oscillations based on the simulated artery bifurcation model comprising a straight tube, and their results showed that low wall shear stress occurred in the bifurcation locations. Nordgaard et al (2010) in their recent report studied WSS in the remodeled left coronary artery and stated that low WSS was found in regions of low flow rate. Again, our analysis is consistent with these observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OSI parameter was defined as in Ku et al 20 A maximum value of 0.5, shows that WSS ¡ is fully changing the direction during the cardiac cycle, which usually describes a complex pulsatile flow. 21 We analyzed the velocity and WSS parameters at peak systole in the fourth cardiac cycle and the OSI during the entire fourth cycle. We chose the peak systole for the error analysis because of the larger errors compared with other time points in the cardiac cycle.…”
Section: Hemodynamic Parametersmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) is the most common method to explore complex flow mechanics and to investigate the WSS distribution in vessels, including coronary arteries and bypass grafts (Nordgaard et al, 2010). Combining various topographic and anatomic features with real and theoretical hemodynamic conditions using computer based modeling provides a mechanism to investigate these potential interactions (Ricotta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%